Konsep Dasar Dalam Sistem Keuangan Syariah - Ilyas, Rahmat (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
Dinul Islam is a comprehensive living system that Allah swt down through His Apostle. Which includes aqidah, ubudiah, mu'amalah, mu'asyarah and morals that guide people so life is full of glory. Comprehensive concept means comprehensive rules that encompass various aspects of life, whether of dimension of belief (aqidah), ritual of self-servant (ubudiah), and social aspect ie mu'amalah, mu'asyarah and morals. In everyday life, economy is the wheel of life as a container to meet the material needs of human beings, both in individual life, and social. Islam leads its people to embrace and practice Islamic teachings in a kaffah (comprehensive / comprehensive) in all aspects of life.